HUBUNGAN KETERGANTUNGAN MEDIA SOSIAL GENERASI Z DENGAN KECEMASAN SOSIAL - Alifah Nurul Fadilah; Nurus Sa’adah (CONS-IEDU, 2021)
In the digital era, technologies cannot be defined away from people's daily lives, especially students. The students who is active users of social media, use social media as an intermediary for their social life, so it is not uncommon for causing addiction to social media. This addiction creates a new psychological disorder of its users; social anxiety disorder. Social anxiety arises from the lack of human courage to meet the real social environment. This study tries to see how much does influence of social media addiction on social anxiety experienced by students. This study uses the Literature Review method. The research shows that almost 20% of the samples says that there is a relationship between social media addiction and social anxiety. This variable cannot stand alone because of other factors that also affect social anxiety